The acute effects of self-myofascial release and static stretching on hamstring flexibility / Syahizwan Tahar - Tahar, Syahizwan (Faculty of Sport Science and Recreation, 2015)
Introduction: Flexibility is the term commonly used to refer to the movement of a joint from full flexion to full extension (full range-of-motion). Commonly, people are performing stretching to increase flexibility, range-of-motion (ROM) and reduce injury. Objective: The purpose of the study was to compare the acute effects of Self Myofascial Release (SMR) and Static Stretching (SS) on hamstring flexibility. Methodology: Eighteen male and twelve female subjects were tested under two flexibility treatment, including I) Myo-Fascial Release, and having a washout period for ten days then continues with 2) static stretching. Following both conditions, subjects were tested for flexibility with sit and reach test. The data were analyzed using SPSS statistical software. Paired sample t-test was used to assess the differences between SMR and SS. Result: There were no significant difference between SMR and static stretching (p = 0.956). Therefore, no such difference in flexibility performance increment. Conclusion: As a conclusion, SMR and static stretching having the same positive effects on hamstring flexibility.